Inhibition of ADP-induced P-selectin Expression and Platelet-Leukocyte Conjugate Formation by Clopidogrel and the P2Y12 Receptor Antagonist AR-C69931MX but not Aspirin - Storey, Robert F.; Judge, Heather M.; Wilcox, Robert G.; Heptinstall, Stan (Thrombosis and Haemostasis, 2002)
Platelet-leukocyte interactions are recognised to have pro-inflammatory effects, which may be important in the pathophysiology of ischaemic heart disease. Clopidogrel and the novel intravenous antithrombotic agent AR-C69931MX act at the level of the platelet P2Y12 receptor, which is known to amplify platelet activation, aggregation and other responses induced by numerous platelet agonists. We studied the effects of clopidogrel and aspirin on ADP-induced platelet-leukocyte conjugate formation and P-selectin expression in healthy volunteers. The effects of clopidogrel and AR-C69931MX administered to patients with ischaemic heart disease were also assessed. AR-C69931MX and aspirin were also studied in vitro. Clopidogrel and AR-C69931MX suppressed ADP-induced platelet aggregation, P-selectin expression and platelet-leukocyte conjugate formation whereas aspirin had no inhibitory effect. These effects of clopidogrel and AR-C69931MX may confer therapeutic benefits in the management of acute coronary syndromes.
Keywords: Blood platelets; platelet aggregation inhibitors; adenosine diphosphate; acute coronary syndromes; leukocytes; AR-C69931MX